Prevalence and Implications of “Must‐Kill” Angling Regulations for the Management of Invasive Fishes - Kevin A. Adeli; Bryan D. Neff; Steven J. Cooke (Fisheries Management and Ecology, 2026)
Freshwater biodiversity is increasingly threatened by invasive species, which can disrupt native fish populations and the fisheries they support. Must‐kill regulations, which prohibit the live release of invasive fish caught by recreational anglers, are a management strategy that can be implemented to limit the negative effects of invasive fish populations. Our review of angling regulations around the globe revealed that must‐kill regulations for numerous species were frequently enacted in countries including Canada, Japan, and the USA. Suggested benefits of must‐kill regulations included limiting invasive species population size and preventing their dispersal, among others. While these benefits were plausible, we found no rigorous assessments of their effectiveness. Moreover, must‐kill regulations can introduce concerns such as angler opposition and species misidentification. Here, we bolstered sparse evidence with anecdotes and perspectives to identify potential advantages and drawbacks of must‐kill regulations. We also provided guidelines for implementing must‐kill regulations that emphasize strategies to increase the likelihood of success while minimizing unintended consequences. Specific guidelines vary depending on management objectives, but generally include a preliminary feasibility and risk assessment followed by post‐implementation monitoring of efficacy and consequences.